Do we cause harm? Understanding the impact of research with young children about their body image. (September 2020) - Damiano, Stephanie R.; McLean, Siân A.; Nguyen, Lilly; Yager, Zali; Paxton, Susan J.
Highlights: The impact on children from participating in body image research is unknown. Parent perceptions of impact on their child's body attitudes were assessed. 96.8-99.5 % of parents reported a positive or no impact on their child. 0.5-3.2 % of parent reported a negative impact on their child. Recommendations for research assessing child body image are provided. Abstract: Although research into the early development of body image and eating behaviors is essential, concerns have been raised about whether their assessment might precipitate body or eating concerns in children. We aimed to identify how parents perceived their young children (under 9 years) had been impacted from involvement in the longitudinal Children's Body Image Development Study (CBIDS) that assessed body image and eating behaviors. Participants were 218 parents (99 % mothers) who completed an online questionnaire assessing whether and why their child discontinued participation in CBIDS, and the perceived impact of participation on children's body image, weight attitudes, language about bodies, internalisation of appearance ideals, peer appearance conversations, dietary restraint, muscle building activities, and physical activity. Impact and reasons for cessation of participation were assessed retrospectively. Almost all parents were positive or neutral about their child's involvement, 0.5%–3.2% of parents perceived a negative impact in an area, and 0.9 % of parents moderately agreed that they regretted participating in CBIDS. Themes for positive and negative aspects of CBIDS involvement were explored using thematic analysis. Although research is essential to guide development of prevention strategies, this study highlights the need to implement safeguards to ensure a positive experience for all children.